An Unusual Sinonasal Tumor: Soft Tissue Perineurioma - Fang, W.S.; Emerson, L.L.; Hunt, J.P.; Salzman, K.L. (American Journal of Neuroradiology, 2009)
SUMMARY: Soft tissue perineuriomas are an unusual type of peripheral nerve sheath tumors distinct from schwannomas and neurofibromas, with interesting histologic findings. They are not well characterized on radiographic examination. We report this case of a patient with sinonasal perineurioma to help define the imaging and pathologic features of this rare head and neck tumor.